(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2020)
The objective of the present study was to evaluate walking velocity of middle-age adults and older adults. Ten adults (5 middle age adults and 5 older adults) were recruited from a local community. They were all physically healthy and not injured in the last 6 months. Their whole body landmark position data were collected during subsequent 5-minute walking on a straight track (15m long). The results indicated that walking velocity of middle-age adults were faster than that of older adults during their natural gait. The study concluded that middle-age adults’ likelihood of falls may be higher than older adults’ likelihood of falls.